(untitled) (AYUSHDHARA, 2024)
Adenomyosis is commonly diagnosed benign condition, major symptoms of these are causes the uterus to thicken and enlarge sometimes up to double or triple its usual size. Adenomyosis may lead to menstrual pain, excessive or extended bleeding with clots, and abdominal or pelvic discomfort. Treating adenomyosis is a challenge hormonal treatment at last hysterectomy has been the only way to treat the condition. But in that scenario Ayurveda can provide a better treatment. Adenomyosis is a prevalent gynecological disorder marked by endometrial tissue being embedded within the myometrium, often resulting in severe symptoms like painful menstruation, heavy bleeding, and infertility. In Ayurveda, adenomyosis is comparable to Udavartini yonivyapada. In the Ayurvedic text, 20 Yoni Vyapads are explained, among them, Vipluta is one of them characterized by constant pain associated with other pains of Vata Prakopa. So this disease can be considered as Vipluta Yonivyapad and treat it with the same line of treatment, which has promising results. This review study intends to review adenomyosis and its Ayurvedic perspective preventive and curative aspects.